Sayyid Qutb’s Interpretation of Jihad in Q.S An-Nisa Verse 94: A Study of the Tafsir Fi Zhilal Al-Qur’an - Syitaul Fuadiah; Novali Kholid; Izza Muhtafidz; Andi Rosa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study analyzes Sayyid Qutb’s interpretation of Surah An-Nisa: 94 in Fi Zhilal Al-Qur’an, focusing on the concept of jihad he presents. Surah An-Nisa: 94 emphasizes the principle of caution in warfare and the importance of justice and morality in human relations. Sayyid Qutb interprets this verse by highlighting that jihad is not limited to physical warfare, but also a struggle to uphold justice and moral values in social life. This study uses a descriptive qualitative approach with textual and thematic analysis to explore the meaning of jihad in Qutb’s contextual perspective. The findings show that Qutb views jihad as an ethical struggle, not mere violence. Qutb’s thinking offers a new perspective on jihad that is more moderate and relevant to the current social-religious challenges, emphasizing the principles of justice, morality, and humanity in the struggle for Islam.